2015
DOI: 10.1245/s10434-015-4377-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes of Nerve-Sparing Radical Hysterectomy for Cervical Cancer: A Systematic Review

Abstract: The results showed that the evidence addressing the oncologic safety of NSRH over that of CRH in cervical cancer is neither adequate nor statistically relevant. A properly designed, prospective randomized noninferiority trial is needed to assess the oncologic outcomes of NSRH before this surgical approach is adopted as the standard of care for patients with tumors that have unfavorable prognostic features. Until then, NSRH should be considered primarily for patients with small tumors due to the very low risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
(56 reference statements)
2
32
0
1
Order By: Relevance
“…The traditional radical hysterectomy should be conducted if PNI of cervical cancer was identified. However, some researchers consider tumor size <2 cm, shallow myometrial invasion, and no LVSI as the indications of NSRH (32). In the present study, our multivariate analysis identified that PNI of cervical cancer was associated with LVSI and lymph node metastasis, suggesting that LVSI and lymph node metastasis are independent risk factors for PNI.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The traditional radical hysterectomy should be conducted if PNI of cervical cancer was identified. However, some researchers consider tumor size <2 cm, shallow myometrial invasion, and no LVSI as the indications of NSRH (32). In the present study, our multivariate analysis identified that PNI of cervical cancer was associated with LVSI and lymph node metastasis, suggesting that LVSI and lymph node metastasis are independent risk factors for PNI.…”
Section: Discussionsupporting
confidence: 46%
“…Studies on the safety of NSRN are predominantly focused on the post-operative function of bladder and rectum and sexual activities, however, these studies have a number of limitations such as poor comparison, small sampling size, or shorter follow-up period. Whether NSRH is safer than the traditional radical hysterectomy has not yet been determined (32)(33)(34). Given that PNI of cervical cancer is associated with poor prognosis of cervical cancer patients, NSRH should be carefully recommended for cervical cancer patients with PNI.…”
Section: Discussionmentioning
confidence: 99%
“…As Basaran and colleagues reported that there were neither adequate nor statistically relevant evidence addressing the oncologic safety of NSRH over that of RH, due to the scarcity and heterogeneity of effect estimates in different trials [8]. We focused on the recurrence rate of cervical cancer after NSRH and RH, which was regarded as a main outcome measure.…”
Section: Main Findingsmentioning
confidence: 99%
“…While splanchnic and hypogastric nerve-sparing surgery for cervical cancer (to avoid urinary dysfunction) has been a focus for many groups, the long-term data as to the desired effect are still inconclusive [52]. …”
Section: Other Approaches Under Investigationmentioning
confidence: 99%